Optimization of Liquefied Air Energy Storage System Coupled with Organic Rankine Cycle - Jianshe LI; Yihua DONG; Haihua LUO (Zhongguo dianli, 2020)
Energy storage is an important technical route to solve the intermittence and instability issue of renewable energy generation, such as wind energy and solar energy. Hence in this paper, regarding the low cycle efficiency of conventional liquefied air energy storage system, the organic Rankine cycle is introduced to make use of the compressed heat generated during the liquefaction stage. To construct the liquefied air energy storage model coupled with organic Rankine cycle, the system cycle efficiency and the exergy efficiency in the air energy release and generation stage are set as objective functions. The outlet pressure of compressor unit, the outlet pressure of cryopump, the narrow temperature difference of cold box and the efficiency of heat exchanger are taken as decision variables respectively. And the non-inferior classification genetic algorithm NSGA-II is used for multi-objective optimization. The Pareto optimal frontier curve is then depicted and by virtue of the TOPSIS optimization method, the optimal system design scheme is obtained with the nearest approximation degree in which the corresponding system cycle efficiency is 62.75%.